The moderating role of external private investment on government-sponsored commercialisation R&D - Kim, Zhunwoo; Kwon, Ohsung (Economics and Business Letters, 2024)
The influence of external private investment (EPI) in public R&D is well-known, however, research has yet to understand the significance of it on the success of R&D. We expand upon existing literature by focusing on the effect of EPI in conducting public R&D, and more specifically, suggesting the moderating role of EPI on the commercialisation success with 472 samples from Korean manufacturing firms. Our findings address that EPI positively moderates the relationship between the amount of government fund, the difference of technology readiness level before and after R&D, and the commercialisation success. As a result, this research contributes to a managerial perspective; concluding that public R&D with EPI is both more successful and rewarding.